Radiotracer and particle tracking methods, modeling and scale‐up. Issue 1 (24th November 2016) - Roy, Shantanu
Abstract : Radiotracer techniques are widely used for troubleshooting and detection of pathological flows in industrial reactors. In recent decades, there has been a trend towards using radiotracer techniques for assessing flow field in industrial vessels, likening them to residence time distribution (RTD) measurements. On the other hand, radiation‐based particle tracking techniques such as Radioactive Particle Tracking (RPT) methods have become popular for laboratory investigations flow fields in multiphase reactors. Both the methods have been used to validate respective‐scale phenomenological and CFD models to some success, but in a rather independent and ad hoc fashion and not attempting to link the two techniques as flow interrogators in their respective domains. This communication tries to bridge these two techniques and proposes a way to link the two, and makes a case for using them as complementary techniques for measurements at the two scales, and for validating models at the two scales. © 2016 American Institute of Chemical Engineers AIChE J, 63: 314–326, 2017